The effect of problem solving methods through playing puzzles and blocks on social-emotional development in PAUD Ambon City - Hermelina Abarua (International Journal of Education, Information Technology, and Others, 2022)
This study aims (1) to determine the effect of learning by playing puzzles and blocks using problem solving methods on social emotional development in children at PAUD institutions in Ambon city (2) To determine the effect of learning by playing blocks using problem solving methods on social emotional development in children. at PAUD institutions in Ambon city (3) To determine the effect of differences in learning through playing puzzles and playing blocks using problem solving methods on the socio-emotional development of children at PAUD institutions in Ambon city, examining the differences in the effect of problem solving methods through playing puzzles and blocks on development emotional social in PAUD Ambon City. This research was conducted at the Ambon State Kindergarten. The method used is a quasi-experimental design with Pretest-Posttest Control Group Design. The research concludes that the First. Children in the experimental group, namely the State Kindergarten Training, have the ability to play puzzles using problem solving methods for social emotional development, show very good activity with the lowest score of 20 and the highest score of 50, the average value is 37.4 with a median of 37.5 and a mode of 36. Second. Control group children have the ability to play blocks using problem solving methods on social emotional development, the group shows activity well with the lowest score of 23 and the highest score of 37, the average value is 32.4 with a median of 32.5 and a mode of 30. Third . There is a difference in the average ability to play with children aged 5-6 years between students who are taught using the Problem Solving method with puzzle games and students who are taught using the Problem Solving method by playing with blocks with a price of tcount = 2.78 while ttable with degrees of freedom n1+ n2 -2 = 18 at the significance level of = 0.05 in 1.73 then tcount > ttable, this means that the difference between the two means is significant at the 0.05 level. It can be concluded that there is a difference in the average social emotional ability of early childhood play concepts in the experimental group and the control group. Thus, it can be concluded that there is an effect of the Problem Solving method with puzzle games and the Problem Solving method by playing blocks on the emotional social skills of children aged 5-6 years in PAUD Ambon City.